Media Massa sebagai Sarana Dakwah Kontemporer - Qudratullah Qudratullah (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
Da'wah is often synonymous with speaking on the stand by facing the crowd and conveying messages of kindness. But, as the development of mass media, da'wah is not a product that is always delivered on the stand. The mass media is part of the innovation of delivering messages of da'wah. The existence of mass media provides a new atmosphere for the delivery of messages that are more dynamic and flexible, of course, keep up with the times. The use of mass media as a means of contemporary da'wah is increasingly providing great opportunities to all levels of society who want to invite and convey goodness which in this case is preaching activities. A person can convey messages of goodness through writing (qalam), oral and behavior or actions (things) with audio visual recordings on online media and social media such as Instragram, Facebook, You Tube, short films, radio, TV and so on. The number of users of diverse social media is a sign that preaching must evolve into an activity that invites goodness with a more innovative and creative appeal. So that the public or mad'u will choose what media will be used in receiving messages from da'i. Even so, the use of mass media as a means of propaganda is not easy. There are many things that need to be considered by the perpetrators of propaganda so that the propaganda that is done can go well and achieve its goals. Good management is needed in preparing content that is wrapped in an attractive manner so that people are not bored with the way of delivering da'wah and its contents are almost the same. Da'i are required to be extra active, innovative and creative in preaching on social media, clever in choosing the media to be used, and proficient in the use of existing technology and understanding the condition of mad'u as an object of preaching that will receive propaganda messages through response to changing patterns thought and behavior. Keywords: Da'wah, Mass Media, Contemporary, Da'i, Mad'u, Means. Dakwah, sering kali identik dengan berbicara di atas mimbar dengan menghadapi orang banyak dan menyampaikan pesan-pesan kebaikan. Namun seiring perkembangan media massa, dakwah bukanlah produk yang selalu disampaikan di atas mimbar. Media massa menjadi bagian dari inovasi penyampaian pesan-pesan dakwah. Keberadaan media massa memberikan suasana baru terhadap penyampaian pesan-pesan dakwah yang lebih dinamis dan fleksibel, tentunya mengikuti perkembangan zaman. Penggunaan media massa sebagai sarana dakwah kontemporer semakin memberikan peluang yang besar kepada seluruh lapisan masyarakat yang ingin mengajak dan menyampaikan kebaikan yang dalam hal ini adalah kegiatan dakwah. Seseorang dapat menyampaikan pesan-pesan kebaikan melalui tulisan (kalam), lisan dan perilaku atau perbuatan (hal) dengan rekaman audio visual di media online dan media sosial seperti Instragram, Facebook, You Tube, film pendek, tv radio dan sebagainya. Banyaknya pengguna media sosial yang beragam menjadi tanda bahwa dakwah haruslah berevolusi menjadi sebuah kegiatan yang mengajak pada kebaikan dengan daya tarik yang lebih inovatif dan kreatif. Sehingga dengan begitu masyarakat atau mad’u akan memilih media apa yang akan digunakan dalam menerima pesan-pesan dakwah dari da’i.Meski begitu, penggunaan media massa sebagai sarana dakwah tidaklah mudah. Ada banyak hal yang perlu diperhatikan oleh para pelaku dakwah agar dakwah yang dilakukan dapat berjalan dengan baik dan mencapai tujuannya. Dibutuhkan manajemen yang baik dalam mempersiapkan konten-konten yang dibungkus secara menarik sehingga masyarakat tidak bosan dengan cara penyampaian dakwah dan isinya yang hampir sama. Da’i dituntut ekstra aktif, inovatif dan kreatif dalam melakukan dakwah di media sosial, pandai dalam memilih media yang akan digunakan, dan cakap dalam penggunaan teknologi yamg ada serta memahami kondisi mad’u sebagai objek dakwah yang akan menerima pesan dakwah melalui respon perubahan pola pikir dan perilaku. Kata Kunci: Dakwah, Media Massa, Kontemporer, Da’i, Mad’u, Sarana.